Patient safety and safety culture in managers of health care institutions in a health care network - Borneo Cantalicio, Eler (2020)
Objective. To determine the relationship between the patient safety culture in managers and patient safety. Methods. A correlation design study has been carried out with 55 managers and Health Services Provider Institutions (IPRESS) of the Huanuco Health Network, during the years 2019 and 2020. Apatient safety culture scale and a patient safety checklist were used. Pearson's r correlation test was used in the inferential analysis. Results. 90.9% (50) of the IPRESS showed low-level patient safety and 49.1% (27) of the IPRESS managers showed a negative patient safety culture. On the other hand, the culture of patient safety in managers is significantly related to the patient safety of IPRESS. In addition, patient safety is significantly related to the dimensions of the patient safety culture in managers: organizational commitment, strategic planning, information management, professional involvement, patient and family involvement; all with a p ≤ 0.05. Conclusions. Low patient safety culture values predominated in managers associated with low patient safety compliance of the IPRESS of the Huanuco Health Network.